Feedback and formative assessment—looking backwards to move forward - Nora McCarthy; Karen Neville; Andrew Pope (Discover Education)
Abstract The terms ‘feedback’ and ‘formative assessment’ are ubiquitous in education, but their conceptual boundaries are ill-defined. This perspective piece explores the meaning of ‘feedback’ and ‘formative assessment’, revealing the entanglement and confusion that exists between these two terms. An argument for clarity of terms is made, to avoid ambiguity and to create a common language. A suggestion is made to re-embrace the original definition components of ‘feedback’, as all of the original parameters of this term, when well established in industry and biology, did not migrate into education. Incorporating the original definition components into the current definition of ‘feedback’ in education circles may negate the need for the term ‘formative assessment’ altogether, which carries with it the inevitable negative connotations associated with the word assessment. Words matter. Medical education, with the introduction of competency-based medical education (CBME) and entrustable professional activities offers a timely opportunity to re-visit such terms, with ‘feedback’ and ‘formative assessment’ being central to these processes. While we use medical education as an example to explore how looking backwards and incorporating all aspects of the original feedback definition can help us to move forward with clarity of terms, we mainly seek to bring new perspectives and hope to encourage necessary conversations on ‘feedback’ and ‘formative assessment’ entanglement.